SIMULTANEOUS LAPAROSCOPIC OPERATIONS IN COMBINATION WITH GYNECOLOGICAL AND SURGICAL PATHOLOGY - Martynenko, V.B.; Hromova, A.M.; Sheiko, V.D.; Nesterenko, L.A.; Zezekalo, V.M.; Orlova, Yu.A.; Talash, V.V.; Kachailo, I.A. (World of Medicine and Biology, 2023)
Laparoscopic gynecology has been used worldwide over the last few decades. Many surgical interventions previously performed laparotomically use minimally invasive laparoscopic techniques. Gynecological diseases often occur with other pathologies of internal organs that require surgical treatment. Simultaneous interventions have numerical advantages compared to traditional methods of surgical treatment. As a result of the analyzed clinical data of the conducted research, it can be stated that the simultaneous operations performed to solve gynecological and general surgical pathologies had a course similar to traditional surgical interventions. No cases of development of complications or adverse events were recorded. All patients received the maximum possible amount of treatment with the elimination of more pathological processes, which significantly improved their quality of life.
Keywords: gynecology; simultaneous operations; operative treatment; surgery; laparoscopic operation